Application of E-Office in Mail Management (Study at a Vocational High School Office) - Vishwani Amisa; Agus Sugiarto; Lelahester Rina (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
The e-office system is useful to minimize the use of paper (paperless), and to make storage and processing the information at the office become centralized easier. The purpose of this research is to know about how the e-office management at a Middle School Administration Office in Salatiga City and to know about the difficulties and also challenges in the implementation the processing of e-office. This method of that used in this research are the descriptive and qualitative approach. The result of the research shows that the processing of mail management at the SMK Kristen Bisnis Salatiga uses two systems. Manually and electronic, but the implementation is still dominated by the manual system. The mail processing with the electronic system at a Middle School Administration Office in Salatiga City is still limited. But nowadays, it adapts to use electronic system during pandemic COVID-19. This difficulty is natural and reasonable and often occured. But the most important is how the school organizes and manages it, also give the best specific solution.